PENGARUH INDEPENDENSI DAN PROFESIONALISME TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTANPUBLIK MAKASSAR - Ibrahim Ibrahim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aim to determine (1) the positive influence of independence on audit quality in the public accounting firm in Makassar, (2) Determine the influence of professionalism on audit quality in public accounting in Makassar and (3) Effect of independence and professionalism of the quality audit at accounting firm public in Makassar. The analytical method used mainly in this research is using test instruments that test the validity and reliability test, also using inferential analysis is the method of linear regression and classical assumption in the test questionnaire. The results of this study are (1) independent variables (X1), independence is not positive and significant impact on audit quality equal to (0.382) with a significant level (0.705). It means independence for auditors is very important to note although there was positive and significant effect on audit quality. (2) Variable Professionalism (X2), professionalism is not positive and significant impact on audit quality equal to (0.978) with a significant level (0.337). This means professionalism for auditors is very important to note although there was positive and significant impact on audit quality, and (3) Based on the test results F independence and professionalism significantly influence jointly on audit quality